Polarographic Estimation of Silver and Selenium in Soil Samples Adjacent to Khetri Copper Mines in Presence of 2,3-Dihydroxy Pyridine - Sharma, Jaswant; Mukherjee, S.K. (Asian Journal of Chemistry, 2010)
Polarographic estimation of silver and selenium in eight different soil samples collected in the vicinity of Khetri Copper Project, Rajasthan, have been reported using 2,3-dihydroxy pyridine as a complexing agent.